Coulson & Richardsons Chemical Engineering Vol.III: Chemical and Biochemical Reactors and Process Control - Richardson (J F); Peacock (D G) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2006)
Chemical Engineering
22.5
Keywords: Chemical Engineering